The Training and assistance of the Awik-Awik Teluk Jor (LPATJ) Enforcement Institution in the Management of Water Areas in Jerowaru District East Lombok Regency - Alfian Pujian Hadi; Dewi Putri Lestari; Firman Ali Rahman; Bukhori Muslim (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2020)
Abstract: This activity aims to increase the knowledge of community who are members of the Teluk Jor Awik-awik Institute (LPATJ/ Lembaga Penegak Awik-Awik Teluk Jor) through training and assistance in the management of marine areas. The training and mentoring activities consist of discussion of awik-awik Teluk Jor material, discussion of the implementation of awik-awik during 2013-2020 and the challenges faced, as well as follow-up for the effectiveness of the implementation of awik-awik. The method used is focus group discussion (FGD). Activities produce 1). The material contained in the awik-awik Teluk Jor needs to be refined according to the current conditions so that it will facilitate the implementation of awik-awik. 2) The implementation of awik-awik is quite effective in suppressing the rate of decline in the quality of marine resources in Jor Bay, however, efforts are needed to increase socialization and awareness to the parties, especially people who do not understand awik-awik, which is a collective agreement in protecting and preserving regional resources of Teluk Jor. 3) The follow-up of the training and assistance is in the form of socialization, assistance to stakeholders, and regular monitoring and evaluation of the implementation of awik-awik at least two times a year so that if there is a violation of awik-awik, decisions can be taken as soon as possible involving the government and the community to stop the occurrence of violations or damage. Key words: Awik-awik, Assistance, Socialization, Coastal, Teluk Jor